Co-production of hydrogen and power from black liquor via supercritical water gasification, chemical looping and power generation. (February 2019) - Ajiwibowo, Muhammad W.; Darmawan, Arif; Aziz, Muhammad
Abstract: An integrated system to harvest efficiently the energy from the waste of pulp mill industry, which is black liquor (BL), is proposed and evaluated. The proposed system consists of the supercritical water gasification (SCWG) of BL, syngas chemical looping, and power generation. To minimize the exergy loss throughout the system and to optimize the energy efficiency, process design and integration is conducted by employing the principles of exergy recovery and process integration methods. Hydrogen is set as the main output, while power is produced by utilizing the heat generated throughout the process. Process simulation is conducted using a steady state process simulator, Aspen Plus. Energy efficiency is defined into three categories: hydrogen production efficiency, power generation efficiency, and total energy efficiency. From process simulation, both of the integrated systems show very high total energy efficiency of about 73%.